2020
DOI: 10.7759/cureus.8638
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Cardiac Involvement in COVID-19

Abstract: Cardiac involvement in coronavirus disease 2019 (COVID-19) commonly accompanies multi-organ system failure with acute respiratory syndrome; however, infrequently myocarditis and pericardial effusions may be isolated, yet fulminant. In this report, we highlight significant variations in cardiac involvement and presentation among patients with COVID-19. This article reports two cases of fulminant myocarditis in COVID-19 positive patients who presented to our facility with contrasting symptoms, laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Echocardiography revealed that the heart was enlarged and the LVEF was significantly decreased. Bedside chest radiographs showed typical ground-glass changes indicative of viral pneumonia [ 78 83 ]. Although no direct data are available showing the presence of NETs in the heart, increased levels of cell-free DNA, MPO-DNA complex, and citH3 in the blood and involvement of NETs in lung autopsy indicate that COVID-19 activates NETosis [ 84 86 ].…”
Section: Netosis In Diseases Inducing Hfmentioning
confidence: 99%
“…Echocardiography revealed that the heart was enlarged and the LVEF was significantly decreased. Bedside chest radiographs showed typical ground-glass changes indicative of viral pneumonia [ 78 83 ]. Although no direct data are available showing the presence of NETs in the heart, increased levels of cell-free DNA, MPO-DNA complex, and citH3 in the blood and involvement of NETs in lung autopsy indicate that COVID-19 activates NETosis [ 84 86 ].…”
Section: Netosis In Diseases Inducing Hfmentioning
confidence: 99%
“…Due to the ST-segment elevation in some cases, suspicion of myocardial ischemia was raised, and many patients underwent a conventional coronary angiography or a coronary computed tomography angiography to rule out coronary stenosis. In all cases, there was no coronary narrowing [14,16,19,33] except for one case which had mild luminal irregularities [29]. Other patients' ECGs showed non-specific ischemic changes such as T-wave inversions [11,26].…”
Section: Diagnostic Testing A) Ecg Findingsmentioning
confidence: 85%
“…In the 29 cases reported, only 2 were found to have right ventricular dysfunction [29,30]. Both cases were in cardiogenic shock and on inotropic and vasoactive support.…”
Section: Echocardiographymentioning
confidence: 99%
See 1 more Smart Citation
“…While the primary concern of this virus is its potentially devastating pulmonary disease, it was quickly determined that there were numerous extra-pulmonary manifestations of this virus, including renal, gastrointestinal, liver, cardiac, mediastinal, neurologic, hematologic, vascular, cutaneous, reproductive, and ocular complications [ 2 ]. A wide variety of pathologies related to cardiac involvement in COVID-19 have been reported [ 3 , 4 ]. In particular, the pericardial disease has been increasingly recognized to complicate the course of illness, given very little direction on management strategies.…”
Section: Introductionmentioning
confidence: 99%